Metabolism and Bioactivation of Corynoline With Characterization of the Glutathione/Cysteine Conjugate and Evaluation of Its Hepatotoxicity in Mice - Liu, Ruijuan; Zhou, Fang; He, He; Wei, Jingyao; Tian, Xin; Ding, Li (Frontiers in Pharmacology, 2018)
Corynoline (CRL), an isoquinoline alkaloid, is the major constituent derived from Corydalis bungeana Herba, which is a well-known Chinese herbal medicine widely used in many prescriptions. The purpose of this study was to comprehensively investigate the metabolism and bioactivation of CRL, and identify the CYP450 isoforms involved in reactive ortho-benzoquinone metabolites formation and evaluate its hepatotoxicity in mice. Here, high resolution and triple quadrupole mass spectrometry were used for studying the metabolism of CRL. Three metabolites (M1-M3) and four glutathione conjugates (M4-M7) of CRL ortho-benzoquinone reactive metabolite were found in vitro using rat and human liver microsomes supplemented with NADPH and glutathione. Four cysteine conjugates (M8-M11) were trapped in mice besides M1-M7. Using human recombinant CYP450 enzymes and chemical inhibitor method, we found that CYP3A4, CYP2C19, CYP2C9 and CYP2D6 were mainly involved in the bioactivation of CRL. Furthermore, CRL had no obvious hepatoxicity and didn’t induce acute liver injuries in the experimental dosage (125 mg/kg-500 mg/kg) used in this study. However, phenomena of abnormal behaviors and low body temperature appeared in mice after drug administration, and three of them were dead. Tissue distribution study of CRL in mice showed that the main target organ of CRL was liver, then kidney, heart and brain. CRL could traverse the blood-brain barrier, and have relative high concentration in brain. So, we surmise that toxicity effect of CRL on other organs may have occurred, and more attention should be paid on the traditional Chinese medicine contained CRL in clinic.